MATEC Web of Conferences - Shevelev, S. A. specialist in the field of heat and power engineering senior lecturer of Tomsk Polytechnic University 1983- (EDP Sciences, 2018)
Numerical investigation of transient distribution of temperature in water drops cooled in cool blast in conditions typical for high capacity evaporative water cooling towers has been done. Water drops cooling through thermal conductivity and water evaporation has been taken into consideration. It has been proved that the analysis of temperature distribution along the radius of water drop increases reliability of evaluation results of average temperature of water drops when they are cooled. Effect of water steam concentration in steam-gas mixture layer surrounding a water drop on water cooling towers efficiency has been evaluated.